Follistatin‐like protein 1 enhances NLRP3 inflammasome‐mediated IL‐1β secretion from monocytes and macrophages. Issue 5 (20th February 2014) - Chaly, Yury; Fu, Yu; Marinov, Anthony; Hostager, Bruce; Yan, Wei; Campfield, Brian; Kellum, John A.; Bushnell, Daniel; Wang, Yudong; Vockley, Jerry; Hirsch, Raphael
<x xml:space="preserve">Abstract</x> Follistatin‐like protein 1 (FSTL‐1) is overexpressed in a number of inflammatory conditions characterized by elevated IL‐1β. Here, we found that FSTL‐1 serum concentration was increased threefold in patients with bacterial sepsis and fourfold following administration of LPS to mice. To test the contribution of FSTL‐1 to IL‐1β secretion, WT and FSTL‐1‐deficient mice were injected with LPS. While LPS induced IL‐1β in the sera of WT mice, it was low or undetectable in FSTL‐1‐deficient mice. Monocytes/macrophages, a key source of IL‐1β, do not normally express FSTL‐1. However, FSTL‐1 was found in tissue macrophages after injection of LPS into mouse footpads, demonstrating that macrophages are capable of taking up FSTL‐1 at sites of inflammation. In vitro, intracellular FSTL‐1 localized to the mitochondria. FSTL‐1 activated the mitochondrial electron transport chain, increased the production of ATP (a key activator of the nod‐like receptor family, pyrin domain containing 3 (NLRP3) inflammasome) and IL‐1β secretion. FSTL‐1 also enhanced transcription of the NLRP3 and procaspase 1 genes, two components of the NLRP3 inflammasome. Adenovirus‐mediated overexpression of FSTL‐1 in mouse paws led to activation of the inflammasome complex and local secretion of IL‐1β and IL‐1β‐related proinflammatory cytokines. These results suggest that FSTL‐1 may act on the NLRP3 inflammasome to promote IL‐1β secretion from monocytes/macrophages.